Closed loop obstruction of small bowel: CT signs predicting successful non-surgical treatment. Issue 161 (April 2023) - Kim, Hye Ri; Lee, Yedaun; Kim, Jieun; Baek, Tae Wook; Kim, Hyunwoong; Son, Jung Hee; Park, Eun Joo; Kim, Seung Ho
Highlights: Conservative treatment could be initially suggested in non-strangulated closed-small bowel obstruction. Careful patient selection for conservative treatment is mandatory in closed-loop small bowel obstruction. The distance between the transition zone (>1cm) and low grade of obstruction are independent predictive CT findings of successful conservative treatment in closed-loop small bowel obstruction. The combination of both CT findings could suggest an attempt for conservative treatment. Abstract: Purpose: To clarify the computed tomography (CT) findings related to successful conservative treatments in patients with closed-loop small bowel obstruction (CL-SBO) without evidence of bowel strangulation. Methods: Sixty-four patients (71 CT scans) diagnosed with CL-SBO by CT and received initial conservative treatments from May 2010 to August 2020 were retrospectively included. Two blinded radiologists reviewed the CT findings, including the transition zone (number, distance, and location), maximum bowel diameter, mesenteric haziness, mesenteric fluid, increased unenhanced bowel wall attenuation, decreased bowel wall enhancement, small bowel feces sign, whirl sign, bowel wall thickening, ascites, and degree of obstruction. The findings of the success and failure groups of conservative treatment were compared. Interobserver agreement was assessed for all findings. Results: Among the 71 cases, conservative treatments were successful in 42 cases (59 %) but failed in 29 cases (41 %). In multivariable analyses, the distance between the transition zones (>1 cm) and low-degree obstruction were independently associated with successful conservative treatments, with odds ratios of 6.23 and 3.52, respectively. The combination of these two CT findings exhibited a specificity of 89.7 % with a positive likelihood ratio of 3.01. Interobserver agreement of the degree of obstruction and the distance between the transition zones was almost perfect (ĸ = 0.814 and 0.914, respectively). Conclusions: The distance between the transition zones (>1 cm) and low-grade obstruction are independent CT predictors of successful conservative treatments in CL-SBO patients. Initial conservative treatments are recommended for patients with both CT findings.